Melampaui Daur Ulang: Menanamkan Ekonomi Sirkular dan Nilai Sosial dalam UMKM Perkotaan di Malang - Siti Markhamah; Budi Eko Soetjipto (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2025)
Growing global awareness of environmental issues has led to the increasing adoption of circular economy principles as a practical approach to building efficient and sustainable systems. In Indonesia, particularly in Malang City, micro, small, and medium enterprises (MSMEs) play a vital role in the national economy, contributing over 60% to the gross domestic product (GDP) and employing more than 97% of the workforce. This study aims to examine the relationship and influence of green technology adoption and human resource (HR) training on customer satisfaction, within the context of resource optimization through circular economy practices. Using a quantitative approach, the study surveyed 100 MSMEs selected through simple random sampling to ensure sectoral diversity and minimize sampling bias. Data were processed using Statistical Package for the Social Sciences (SPSS) software. The results indicate that HR training does not have a significant effect on customer satisfaction among MSMEs in Malang City. In contrast, the implementation of green technology and circular economy practices positively contributes to performance improvement, particularly when linked to customer satisfaction and sustainability outcomes across economic, environmental, and social dimensions.